2009
DOI: 10.1080/08870440801998970
|View full text |Cite
|
Sign up to set email alerts
|

Do I feel sadness, fear or both? Comparing self-reported alexithymia and emotional task-performance in children with many or few somatic complaints

Abstract: Children with many somatic complaints seem to report problems with emotion identification and communication ('alexithymia'). The aim of this study was to verify whether children with somatic complaints do indeed show signs of alexithymia. We compared 35 children (M age ¼ 10.99, SD ¼ 13 months) with many somatic complaints with 34 children (M age ¼ 11.03, SD ¼ 12 months) reporting few complaints on the basis of a self-report alexithymia scale and tasks that require the skill to identify and communicate emotions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 25 publications
0
27
0
3
Order By: Relevance
“…The hypothesis is in line with Demjen et al [59], who said that affective distress and difficulty in expressing feelings correlate with the “dimensions” of headache, such as intensity and duration of attacks. This reminds us of a recent study investigating alexithymia that compared children with numerous somatic complaints with cases with few somatic complaints: the former had difficulty communicating negative internal states and experiencing indefinable internal states, as well as revealing greater intensities of fear and sadness [60]. …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The hypothesis is in line with Demjen et al [59], who said that affective distress and difficulty in expressing feelings correlate with the “dimensions” of headache, such as intensity and duration of attacks. This reminds us of a recent study investigating alexithymia that compared children with numerous somatic complaints with cases with few somatic complaints: the former had difficulty communicating negative internal states and experiencing indefinable internal states, as well as revealing greater intensities of fear and sadness [60]. …”
Section: Discussionmentioning
confidence: 98%
“…Alexithymia would thus represent a risk factor for the onset of medical or psychiatric, organic or functional disorders [47, 48, 60]. …”
Section: Discussionmentioning
confidence: 99%
“…Ciarrochi et al (2007) showed that children who tend to make more depressive appraisals for events reported more fear and sadness one year later. Moreover, Jellesma et al (2009) showed that children with many somatic complaints described more and stronger negative emotions in response to various scenarios than children with few complaints. Robinson, Garber, and Hilsman (1995) demonstrated that negative appraisals are positively associated with depressive symptoms.…”
Section: Children's Appraisals and Internalizing Problemsmentioning
confidence: 97%
“…In the literature on internalizing problems, children's appraisals of situations are often referred to as a potential mediator of (interpersonal) stressors and the development of internalizing problems (e.g., Ciarrochi, Heaven, & Davies, 2007;Jellesma, Rieffe, Terwogt, & Westenberg, 2009). More specifically, when children appraise situations negatively, they also often experience negative affect.…”
mentioning
confidence: 99%
“…The authors found that mood states mediated the relationship between alexithymia and internalizing symptoms, but alexithymia also contributed to internalizing symptoms above the effects of mood, suggesting that an independent relationship with alexithymia and somatization also exists. Yet, in another recent study, Jellesma, Rieffe, Terwogt & Westenberg (2009) found that the children reporting many somatic symptoms did not have an impaired ability to identify emotions, as compared to children reporting few somatic symptoms. However, those reporting many somatic symptoms did have difficulty identifying and communicating negative internal states (i.e., moods) but were better able to identify multiple emotions as compared to children reporting few somatic complaints.…”
mentioning
confidence: 86%